IMPLIKASI FALSAFAH BARAT TERHADAP PEMIKIRAN HUKUM POSITIF - Abdul Gani, Yusra Habib (Al-Qisth Law Review, 2017)
The development of western philosophy has internalized the idea of positive legal thought. Whereas in fact the source of western philosophical thought is derived from the concepts of Islamic philosophy. Therefore, there needs to be a reorientation of the idea of positive legal thought derived from western philosophy to use Islamic philosophy. to free ourselves from the influence of Western philosophical thought, we must not be pursued by condemning, cursing and condemning it, but we dare to compete in a healthy and professional way to create concepts to build civilized civilized society, until the time comes people will come to the conclusion that in all aspects, the thoughts and concepts of building human civilization, Islam is superior to Western philosophy.